Preparation of Superhydrophobic Multiscale Films for Oil-Water Separation in a Harsh Environment. (5th November 2019) - Li, Depeng; Fan, Jinyang; Chen, Jie; Jiang, Deyi
Abstract : The problem of oil-water separation regarding oil-containing brine has been of much concern when using the oil pad water dissolution method to construct salt cavern reservoirs. In this paper, oil-water separation materials with micro-nano hierarchical structure were prepared on different metal substrates using chemical etching and electrophoretic deposition. And hydrophobic materials with a single micro/nano structure were also prepared; then, the surfaces were hydrophobized by various low surface energy modifiers. Thereafter, we analyzed and compared the surface morphology, chemical composition, and wettability of all the materials and found that brine contact angles on hierarchical structure surfaces were above 160° while the diesel was completely diffused. Furthermore, preparation parameters affecting the surface morphology and wettability of micro-nano composite structures were explored. Meanwhile, it was found that the surface of prepared composite structure could still maintain super-hydrophobic/lipophilic properties after exposure in air for 6 months, sliding 60 cm on sandpaper, or immersion in diesel/brine for 48 h. Moreover, the composite structure surface displayed improved corrosion resistance with corrected self-corrosion potential and lower corrosion current density. It was equally observed that the studied materials could be better adapted to the actual context of salt cavern reservoir construction and thus have great application prospects.